Environmental stress, displacement and the challenge of rights protection - Zetter, R; Morrissey, J (Refugee Studies Centre, University of Oxford, 2014)
Examination of migration histories and current politics in Kenya, Bangladesh, Vietnam, Ethiopia and Ghana sheds light on how rights are articulated for groups and individuals displaced in a context of environmental stress and climate change. Both migration and rights are sensitive issues in these case-study countries, and the conjunction of the two is especially sensitive.